2008
DOI: 10.1111/j.1601-5037.2008.00320.x
|View full text |Cite
|
Sign up to set email alerts
|

Survey of medical doctors’ attitudes and knowledge of the association between oral health and pregnancy outcomes

Abstract: There is a need to educate healthcare personnel further about oral health and pregnancy outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
57
2
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 21 publications
(23 reference statements)
9
57
2
5
Order By: Relevance
“…The referral rate (56.5%) in the present study may be considered similar when compared with the findings of Al-Habashneh et al 27 and Owen et al 24 , with rates of 49.7% and 48%, respectively. Our findings underscore the need for promoting collaboration between dental and medical doctors to improve patient outcomes with respect to PD and associated diseases and conditions.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…The referral rate (56.5%) in the present study may be considered similar when compared with the findings of Al-Habashneh et al 27 and Owen et al 24 , with rates of 49.7% and 48%, respectively. Our findings underscore the need for promoting collaboration between dental and medical doctors to improve patient outcomes with respect to PD and associated diseases and conditions.…”
Section: Discussionsupporting
confidence: 70%
“…This finding can be compared with the findings of Al-Habashneh et al 27 which showed that the responders obtained the same information, primarily from magazines. The different findings in the two studies may be explained by their different study populations: our responders were mostly interns and university doctors, whereas the population in the Al-Habashneh et al 27 study focused on general practitioners.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23] Fakat ülkemizde bu konuyla ilgili çalıĢma sayısı oldukça sınırlıdır. Bu bilgilerin ıĢığında biz de çalıĢmamızda, alanında uzman tıp hekimlerinin hastalarında ağız sağlığı ile ilgili izledikleri yaklaĢımları ve periodontal durum ile sistemik durum arasındaki iliĢkiye yönelik farkındalıklarını değerlendir-meyi hedefledik.…”
Section: Introductionunclassified